The Intergenerational Behavioural Consequences of a Socio-Political Upheaval - Alison L. Booth; Xin Meng; Elliott Fan; Dandan Zhang (Institute of Labor Economics (IZA), 2018)
Social scientists have long been interested in the effects of social-political upheavals on a society subsequently. A priori, we would expect that, when traumas are brought about by outsiders, within-group behaviour would become more collaborative, as society unites against the common foe. Conversely, we would expect the reverse when the conflict is generated within-group. In our paper we are looking at this second form of upheaval, and our measure of within-group conflict is the 1966-1976 Cultural Revolution (CR) that seriously disrupted many aspects of Chinese society. In particular, we explore how individuals' behavioural preferences are affected by within-group traumatic events experienced by their parents or grandparents. Using data from a laboratory experiment in conjunction with survey data, we find that individuals with parents or grandparents affected by the CR are less trusting, less trustworthy, and less likely to choose to compete than their counterparts whose predecessors were not direct victims of the CR.
Keywords: C91; N4; 330; preferences; behavioural economics; cultural revolution